Ketosis, ketogenic diet and food intake control: a complex relationship - Paoli, Antonio; Bosco, Gerardo; Camporesi, Enrico M.; Mangar, Devanand (Frontiers in Psychology, 2015)
Though the hunger-reduction phenomenon reported during ketogenic diets is well known, the underlying molecular and cellular mechanisms remain uncertain. Ketosis has been demonstrated to exert an anorexigenic effect via cholecystokinin (CCK) release while reducing orexigenic signals e.g. via ghrelin. However ketone bodies (KB) seem to be able to increase food intake through AMP-activated protein kinase (AMPK) phosphorylation, gamma-aminobutyric acid (GABA) and the release and production of adiponectin. The aim of this review is to provide an overview of our current knowledge of the effects of ketogenic diet (KD) on food control in an effort to unify the apparently contradictory data into a coherent picture.